Adoption from Care International Perspectives on Children's Rights, Family Preservation and State Intervention - Pösö, Tarja; Skivenes, Marit; Thoburn, June (Research in Social Work series, 2021)
"EPDF and EPUB available Open Access under CC-BY-NC-ND. This book explores how children's rights are practised and weighed against parents' rights in a range of countries, and examines how governments and legal and welfare professionals balance those rights in the challenging circumstances following the decision that children cannot grow up in their parents' care. Looking at adoption from care in Europe and the United States, it provides in-depth analysis of concepts of family, contact, the child's best interest principle and human rights in adoption from care across these different socio-political and legal contexts. Taking an international comparative approach to these issues, this book provides best practice evidence on adoption processes and shares learning across country boundaries to help improve outcomes for all adopted children."